K-State Turfgrass Research 2011 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Turfgrass Research 2011 contains results of projects conducted by Kansas State University faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day, August 4, 2011, at the John C. Pair Horticultural Research Center in Olathe, Kan. Articles included in this Report of Progress present summaries of research projects that were completed recently or will be completed in the next year or two. Specifically, this year’s report presents summaries of research on turf and the environment, pest control, and turf evaluations.
Keywords: Turfgrass; Pest management; Buffalograss; Zoysiagrass; Creeping Bentgrass; Kentucky Bluegrass